Inovasi Media Pembelajaran Pendidikan Agama Islam Melalui Media Audiovisual - Tiara Febriani Harahap; Zainal Efendi Hsb (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
Students have different levels of material understanding, including in understandingmonotonous Islamic Education materials using lecture methods. Sometimes students find it difficult to capture what teachers describe, especially in complex materials such as fiqh and long materials such asislamic culturalhistory. Thepurposeofthisresearch is to conducta learning innovationto address students' problems related to material understanding. The innovation that will be discussed in this article is the development of audiovisual media for Islamic Religious Education (PAI). The research method useslibrary research collectedfrom books and journals. With the development of audiovisual media innovation, it is hoped that students can better understand islamic education materials and provide a new atmosphere in learning. As a result of this study with technological developments, accessing audivisual media in learning is easier. The most popular site that provides audiovisual media access is Youtobe. The role of educators in the playback of learning videos as mentors. So that with this medium can shape the effectiveness of student learning.